Using Technology to Conduct Focus Groups With a Hard-to-Reach Population: A Methodological Approach Concerning Male Victims of Partner Abuse in Four English-Speaking Countries - Douglas, Emily M. (Journal of interpersonal violence, 2021)
Research shows that the experiences of male victims of partner abuse (PA) are often denied by the public and the professionals who are charged to support PA victims. Recruiting female victims for research on PA victimization is relatively easy because there are existing structures to serve this group of victims. Thus, male victims are considered a hard-to-reach (HTR) population, and studying them can be difficult. This article focuses on the use of technology to collect qualitative data from male PA victims in an international study focusing on male victims. The researchers used their own professional networks to recruit and screen a convenience sample of male victims of female-to-male PA, in four different English-speaking countries: Australia, Canada, England, and the United States. Four web-based, video-enabled, focus groups were held for each country—for a total of 12 groups and 41 male participants. This article addresses recruitment methods, the use of technology in data collection, protecting the confidentiality of male victims, methods for informed consent, and lessons learned to facilitate future research.